1969
DOI: 10.1029/wr005i001p00084
|View full text |Cite
|
Sign up to set email alerts
|

Runoff Volume Prediction From Daily Climatic Data

Abstract: A two-soil-moisture-reservoir model is developed to improve the estimate accuracy of g runoff-volume-prediction model. Soil moisture accounting in the two reservoirs is an intermediate step to runoff prediction. A decay-type function describes the moisture depletion between days of rainfall. The moisture depletion constant in the function varies by season with soil moisture, pan evaporation, and mean daily temperature. The runoff-prediction equation relates runoff to rainfall and soil moisture at the beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Recharge of bedrock groundwater is controlled in part by the permeability of covering soils and sur®cial deposits, and in part by the transpiration eects of trees and other vegetation. These mechanisms may vary substantially with seasonal changes and with elevation in a steep alpine environment (McGuinness and Harrold 1962;Knisel, Baird and Hartman 1969;Parmele 1972;Woolhiser 1973;Saxton and McGuinness 1982).It was the objective of our study to characterize bedrock recharge and ow mechanisms in the 10.5 km 2 uppermost watershed of the Browns River in northwestern Vermont. In the study area (Figure 1), precipitation increases with elevation.…”
mentioning
confidence: 97%
“…Recharge of bedrock groundwater is controlled in part by the permeability of covering soils and sur®cial deposits, and in part by the transpiration eects of trees and other vegetation. These mechanisms may vary substantially with seasonal changes and with elevation in a steep alpine environment (McGuinness and Harrold 1962;Knisel, Baird and Hartman 1969;Parmele 1972;Woolhiser 1973;Saxton and McGuinness 1982).It was the objective of our study to characterize bedrock recharge and ow mechanisms in the 10.5 km 2 uppermost watershed of the Browns River in northwestern Vermont. In the study area (Figure 1), precipitation increases with elevation.…”
mentioning
confidence: 97%
“…This is important because total pesticide loss depends on the time lapse between rainfall inception and runoff initiation (Wauchope et al 1990). Antecedent soil moisture has the potential to increase runoff volume and reduce time to runoff (Barnett et al 1967;Knisel and Baird 1969).…”
mentioning
confidence: 99%
“…McGuinness and Harrold (1962) found that small-area streamflow at Coschocton, Ohio was regulated primarily by seasonal ET. Knisel and Baird (1969) found they could accurately predict runoff from a 3-acre watershed near Riesel, Texas by using a procedure which predicted soil moisture from ET-related variables,…”
Section: Evapotranspiration As a Hydrologie Componentmentioning
confidence: 99%